Árabe urbano de Rabat. Cuestionario dialectológico - García, Francisco Moscoso (My University, 2006)
We present the results of a dialectal survey carried out in the capital of Morocco amongst three young students. The dialect studied is the urban Arabic of Rabat and we also compare our results with other studies on the UAR and with other dialects of the country which have been analysed up till now.
Keywords: Morocco. Rabat. Arabic Dialectology. Moroccan Arabic. Urban Arabic of Rabat.